2020
DOI: 10.3390/cancers12071737
|View full text |Cite
|
Sign up to set email alerts
|

CXCR4 Inhibition Enhances Efficacy of FLT3 Inhibitors in FLT3-Mutated AML Augmented by Suppressed TGF-β Signaling

Abstract: Given the proven importance of the CXCL12/CXCR4 axis in the stroma–acute myeloid leukemia (AML) interactions and the rapid emergence of resistance to FLT3 inhibitors, we investigated the efficacy and safety of a novel CXCR4 inhibitor, LY2510924, in combination with FLT3 inhibitors in preclinical models of AML with FLT3-ITD mutations (FLT3-ITD-AML). Quizartinib, a potent FLT3 inhibitor, induced apoptosis in FLT3-ITD-AML, while LY2510924 blocked surface CXCR4 without inducing apoptosis. LY2510924 signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 50 publications
1
7
0
Order By: Relevance
“…For example, FLT3-ITD mutation upregulates the expression levels of STAT5 (a regulatory factor for CXCR4 mRNA level), causing an increase in CXCR4 expression on the cell surface in AML ( Cao et al, 2019b ). Besides, LY2510924, a CXCR4 inhibition, could significantly increase the effect of FLT3 inhibitors in the AML cells with FLT3-ITD mutation ( Kim et al, 2020 ). Identifying the common downstream cellular mechanisms of FLT3-ITD and CXCR4-CXCL12 axis helps to further understand the interactions between them from another aspect.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, FLT3-ITD mutation upregulates the expression levels of STAT5 (a regulatory factor for CXCR4 mRNA level), causing an increase in CXCR4 expression on the cell surface in AML ( Cao et al, 2019b ). Besides, LY2510924, a CXCR4 inhibition, could significantly increase the effect of FLT3 inhibitors in the AML cells with FLT3-ITD mutation ( Kim et al, 2020 ). Identifying the common downstream cellular mechanisms of FLT3-ITD and CXCR4-CXCL12 axis helps to further understand the interactions between them from another aspect.…”
Section: Discussionmentioning
confidence: 99%
“…The signal pathways activated by the CXCL12/CXCR4 axis have been demonstrated to show effects in interactions between tumor cells and the microenvironment in AML, and the interactions would cause chemoresistance and AML relapse ( Lee et al, 2017 ; Cao et al, 2019b ). Several recent publications suggest an interaction between FLT3-ITD mutation and CXCL12/CXCR4 axis, and the CXCL12/CXCR4 axis has been proved an important role in the rapid emergence of resistance to FLT3 inhibitors ( Cao et al, 2019b ; Kim et al, 2020 ; Waldeck et al, 2020 ). Although it has been identified that the combination of the FLT3 inhibitor and CXCR4 antagonist could improve the sensitivity of chemotherapy treatment in AML cells ( Jacobi et al, 2010 ; Kim et al, 2020 ), the lack of understanding of the impact on AML cells produced by the interaction between FLT3-ITD mutation and the CXCL12/CXCR4 axis restricts the development of the related research.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…TGF-β expression is upregulated in stromal cells in the AML-BME and contributes to tumor growth and treatment resistance. Silencing of TGF-β in stromal cells co-cultured with FLT3-ITD-AML enhances treatment-induced AML apoptosis and sensitizes AML cells to combination chemotherapy [ 32 ]. Moreover, TGF-β inhibition by small-molecule inhibitors or neutralizing antibodies is a strategy that has been explored to counteract chemotherapy resistance in several malignancies, including AML [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…Monodrug therapy with LY2510924 demonstrated dose-dependent antitumor growth and anti-metastasis activities in leukemia, multiple solid tumor xenograft models, and a breast cancer metastatic model. When used in combination, it increased the efficiency of FLT3 inhibitors in preclinical FLT3-mutated AML models by suppressing TGF-β signaling ( 102 ). Secondly, the feature and advantage of LY2510924 is its high in vivo stability.…”
Section: Macrocyclic Peptides Targeting Extracellular Ppismentioning
confidence: 99%